Fetal megacystis‐microcolon: Genetic mutational spectrum and identification of PDCL3 as a novel candidate gene. Issue 3 (4th August 2020) - Billon, Clarisse; Molin, Arnaud; Poirsier, Céline; Clemenson, Alix; Dauge, Coralie; Grelet, Maude; Sigaudy, Sabine; Patrier, Sophie; Goldenberg, Alice; Layet, Valérie; Tantau, Julia; Fleury, Clémence; et al.
Abstract: Megacystis‐microcolon‐intestinal‐hypoperistalsis syndrome (MMIHS) is a severe congenital visceral myopathy characterized by an abdominal distension due to a large non‐obstructed urinary bladder, a microcolon and intestinal hypo‐ or aperistalsis. Most of the patients described to date carry a sporadic heterozygous variant in ACTG2 . More recently, recessive forms have been reported and mutations in MYH11, LMOD1, MYLK and MYL9 have been described at the molecular level. In the present report, we describe five patients carrying a recurrent heterozygous variant in ACTG2 . Exome sequencing performed in four families allowed us to identify the genetic cause in three. In two families, we identified variants in MMIHS causal genes, respectively a nonsense homozygous variant in MYH11 and a previously described homozygous deletion in MYL9 . Finally, we identified compound heterozygous variants in a novel candidate gene, PDCL3, c.[143_144del];[380G>A], p.[(Tyr48Ter)];[(Cys127Tyr)]. After cDNA analysis, a complete absence of PDLC3 expression was observed in affected individuals, indicating that both mutated transcripts were unstable and prone to mediated mRNA decay. PDCL3 encodes a protein involved in the folding of actin, a key step in thin filament formation. Presumably, loss‐of‐function of this protein affects the contractility of smooth muscle tissues, making PDCL3 an excellent candidate gene for autosomal recessive forms of MMIHS. Abstract :